Prognostic Utility of Initial Lactate in Patients with Acute Drug Overdose: A Validation Cohort - Cheung, Randy (Ann Emerg Med, 2018)
OBJECTIVE: Prior studies suggest the initial Emergency Department (ED) lactate concentration may be an important prognostic indicator for in-hospital mortality from acute drug poisoning. We conducted this cohort study to formally validate the prognostic utility of the initial lactate concentration in a larger, distinct patient population with acute drug overdose. METHODS: This observational, prospective, cohort study was conducted over 5-years at two urban teaching hospitals. Consecutive adult ED patients with acute drug overdose had serum lactate drawn as part of clinical care. The primary outcome was inpatient fatality. Receiver operating characteristics (ROC) were plotted to determine optimal cutpoints, test characteristics, area under the curve (AUC), odds ratios (OR), and 95% confidence intervals (CI). RESULTS: Of 3739 patients screened, 1406 patients were analyzed (56% female, mean age 43.1 years)and 24 died (1.7%). The difference in mean initial lactate concentration was 5.9 mmol/L (CI 3.4–8.1) higher in fatalities compared to survivors. The AUC for prediction of fatality was 0.85 (CI 0.73–0.95). The optimal lactate cutpoint for fatality was ≥5.0 (OR 34.2, CI 13.7–84.2, 94.7% specificity). Drug classes for which lactate had the highest utility were salicylates, sympathomimetics, acetaminophen, and opioids (all AUC ≥0.97); lowest utility was for diuretics and ACE inhibitors. CONCLUSIONS: Initial lactate concentration is a useful biomarker for early clinical decision-making in ED patients with acute drug overdose. Studies of lactate-tailored management for these patient populations are warranted.